PARENTS’ INVOLVEMENT AND ITS EFFECTS ON ENGLISH YOUNG LEARNERS’ SELF- EFFICACY - Christiani Tiwi Sumanti; Retno Muljani (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2021)
The research aimed to describe parents’ involvement to support their children’s self-efficacy development in learning English. As a descriptive  qualitative  study, the research  employed observations on two primary school students of  grade  three,  and  interviewed  their  parents  and  teachers. A set of questions was formulated by the researcher to analyze the influence of parents on their self-efficacy in learning English at home. This study showed that parents' commitment has proven to encourage their children to learn English, and through the Zone of Proximal Development (ZPD) process and learning, particularly their encouragement at home makes the children developed their self-efficacy. Parental participation in English should be taken seriously, particularly in public schools, where there was only a minimum period to learn English at school. It was revealed that parents' involvement in the learning and acquisition of English by the children could contribute positively to their learning achievement and motivation.